Solid Organ Transplantation From SARS-CoV-2–infected Donors to Uninfected Recipients: A Single-center Experience. Issue 2 (13th January 2022) - Jayasekera, Channa R.; Vikram, Holenarasipur R.; Rifat, Zeeshan; Wagler, Josiah; Okubo, Keita; Braaksma, Brandon R.; Harbell, Jack W.; Jadlowiec, Caroline C.; Katariya, Nitin N.; Mathur, Amit K.; Moss, Adyr; Reddy, K. Sudhakar; et al.
Abstract : Background: The risk of donor-derived severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in solid organ (heart, lung, liver, kidney, pancreas, and intestine) transplant recipients is poorly understood. Since hematogenous transmission of SARS-CoV-2 has not been documented to date, nonlung solid organs might be suitable for transplantation since they likely portend a low risk of viral transmission. Methods: Abdominal solid organs from SARS-CoV-2–infected donors were transplanted into uninfected recipients. Results: Between April 18, 2021, and October 30, 2021, we performed transplants of 2 livers, 1 simultaneous liver and kidney, 1 kidney, and 1 simultaneous kidney and pancreas from SARS-CoV-2–infected donors into 5 uninfected recipients. None of the recipients developed SARS-CoV-2 infection or coronavirus disease 2019, and when tested, allograft biopsies showed no evidence of SARS-CoV-2 RNA. Conclusions: Transplanting nonlung organs from SARS-CoV-2–infected donors into uninfected recipients demonstrated no evidence of virus transmission.